2022
DOI: 10.1101/2022.10.19.22281280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prior exposure to antiretroviral therapy among adult patients presenting for HIV treatment initiation or re-initiation in sub- Saharan Africa: a systematic review

Abstract: BackgroundAs countries in sub-Saharan Africa have scaled up access to antiretroviral therapy (ART) for HIV, patient attrition rates of up to 30% per year have created a large pool of individuals who initiate treatment with prior ART experience (non-naïve re-initiators). Little is known about the proportion of non-naïve re-initiators within the population presenting for treatment initiation.MethodsWe conducted a comprehensive, rapid review of recent peer-reviewed reports that presented data on proportions of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Disengagement from HIV care—having started taking ART, but then stopped treatment for a defined period of time—is relatively common: in a large multi‐country study which updated data through tracing, only 67% of people who started ART between 2009 and 2014 were engaged in care at 5 years [5], with similar findings in more recent studies in Zambia, South Africa, Tanzania and eSwatini [6–9]. People initiating ART at clinics are often re‐initiating treatment after a period of disengagement, although clients do not always report previous ART experience: a recent review found that 20−50% of ART patients who present for ART were re‐initiators [10]. Disengagement from ART care jeopardizes individuals and communities from realizing the benefits of “Treat All” [3, 11].…”
Section: Introductionmentioning
confidence: 63%
“…Disengagement from HIV care—having started taking ART, but then stopped treatment for a defined period of time—is relatively common: in a large multi‐country study which updated data through tracing, only 67% of people who started ART between 2009 and 2014 were engaged in care at 5 years [5], with similar findings in more recent studies in Zambia, South Africa, Tanzania and eSwatini [6–9]. People initiating ART at clinics are often re‐initiating treatment after a period of disengagement, although clients do not always report previous ART experience: a recent review found that 20−50% of ART patients who present for ART were re‐initiators [10]. Disengagement from ART care jeopardizes individuals and communities from realizing the benefits of “Treat All” [3, 11].…”
Section: Introductionmentioning
confidence: 63%
“…Moreover, participants in a clinical trial of first-line ART are usually required to be ART-naïve. In contrast, in real-world settings, a significant proportion of individuals presenting for first-line ART are re-initiating therapy and may harbor acquired NRTIassociated DRMs [127][128][129].…”
Section: Art-experienced Plwh With Vsmentioning
confidence: 99%
“…It will be a structured questionnaire designed for primarily quantitative analysis but with some open-ended questions (Extended data -Supplementary file 3). Questions will build on previous work of the AMBIT Project and on the authors' experience in studying retention in HIV care 1,3,[17][18][19] . The questionnaire has eight substantive sections, addressing the respondent's demographics and socio-economic status, HIV testing history, HIV treatment history, current HIV care and treatment experience, other healthcare, preferences for features of treatment delivery, expectations, and costs of seeking care.…”
Section: Prefer Survey Of Client Characteristics and Preferencesmentioning
confidence: 99%